Clinical Efficacy and Safety of Anlotinib Combined with Immune Checkpoint Inhibitors in the Treatment of Advanced Squamous Cell Lung Cancer: A Retrospective Single-Center Study in China - Xu, Bin; Xu, Chunhua; Li, Li; Wang, Yuchao (Current Cancer Drug Targets, 2025)
BackgroundThere is a relative lack of real-world data regarding the treatment of advanced squamous cell lung cancer (SqCLC) with anlotinib.Aims and ObjectiveThis study aimed to investigate the clinical efficacy and safety of combining anlotinib with ICIs for the treatment of advanced SqCLC.MethodsSixty patients with advanced SqCLC from December, 2017 to December, 2022, were retrospectively recruited in the final analysis. The overall survival (OS), adverse events (AEs), and short-term clinical effectiveness, including complete remission (CR), partial remission (PR), stable disease (SD), and progression disease (PD) of the study populations, were observed. Objective response rate (ORR) was defined as the combined percentage of CR and PR in all patients. Disease control rate (DCR) was defined as the combined percentage of CR, PR, and SD in all patients. Subgroups were classified based on age (<65 or ≥65), sex (female or male), and the eastern cooperative oncology group (ECOG) score (0-1 or 1-2).ResultsThe median age of the study population was 65 years, and 41 (68.3%) of the participants were male. ORR was 21.67%, and DCR was 83.33%. The median PFS and OS were 7.5 and 19.5 months, respectively. Furthermore, the Kaplan-Meier curves demonstrated no significant difference (P >0.05) in PFS and OS between different age groups, sex, and ECOG scores. Bone marrow suppression was the most common AE, followed by immune pneumonia.ConclusionThe findings of this study confirmed the effectiveness and safety of anlotinib and ICIs for advanced SqCLC.
Keywords: advanced squamous cell lung cancer